Asymptomatic Healthcare Worker PCR Screening during SARS-CoV-2 Omicron Surge, Germany, 2022 - Ralph Bertram; Wolfgang Hitzl; Eike Steinmann; Joerg Steinmann (Emerging Infectious Diseases, 2023)
During 2022, a total of 9,515 asymptomatic healthcare workers of a large hospital in Germany underwent SARS-CoV-2 PCR screening twice weekly. Of 398,784 saliva samples, 3,555 (0.89%) were PCR positive (median cycle threshold value 30). Early identification of infected healthcare workers can help reduce SARS-CoV-2 transmission in the hospital environment.